2016
DOI: 10.1002/mats.201600009
|View full text |Cite
|
Sign up to set email alerts
|

Model Discrimination in Copolymerization Using the Sequential Bayesian Monte Carlo Method

Abstract: The term model discrimination, as used in this paper, refers to the sequential process of designing experi mental conditions, carrying out the new experiment and analyzing competitive models. Experiments are designed in these procedures to provide the maximum possible information from the minimum number of experiments with respect to discrimination between the rival models.Burke et al. [1][2][3][4] studied the application of statistical model discrimination methods to terminal and penultimate copoly merization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Masoumi et al [40,41] used a new approach to investigate model discrimination, based on the sequential Bayesian Monte Carlo model discrimination (SBMCMD) method. In a later work, Masoumi et al [42] applied SBMCMD in simulated copolymerization systems to compare its performance with the performances of other statistical discrimination methods already used in previous studies, as reported by Burke et al [19] The authors also used the Hsiang and Reilly [22] method to analyzed the same copolymerization systems and compared the obtained results with the ones presented in previous works. According to their results, the SBMCMD method could select the best model with fewer experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Masoumi et al [40,41] used a new approach to investigate model discrimination, based on the sequential Bayesian Monte Carlo model discrimination (SBMCMD) method. In a later work, Masoumi et al [42] applied SBMCMD in simulated copolymerization systems to compare its performance with the performances of other statistical discrimination methods already used in previous studies, as reported by Burke et al [19] The authors also used the Hsiang and Reilly [22] method to analyzed the same copolymerization systems and compared the obtained results with the ones presented in previous works. According to their results, the SBMCMD method could select the best model with fewer experiments.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] A sequential Bayesian Monte Carlo model discrimination (SBMCMD) method was first introduced in Masoumi et al, [8] developed further in a second paper by Masoumi et al, [9] and used for discrimination between copolymerization models in a third paper from the same authors. [10] SBMCMD benefits from advantages of both being a sequential model discrimination method and using Markov Chain Monte Carlo (MCMC) techniques. This makes it a flexible method applicable to all types of models regardless of their structure (nested vs nonnested, or linear vs nonlinear).…”
Section: Introductionmentioning
confidence: 99%